Activation of EP4 receptor limits transition of acute to chronic heart failure in lipoxygenase deficient mice - Kain, Vasundhara (Theranostics, 2021)
Aim: Immune responsive 12/15 lipoxygenase (12/15LOX)-orchestrate biosynthesis of essential inflammation-resolution mediators during acute inflammatory response in post-myocardial infarction (MI). Lack of 12/15LOX dampens proinflammatory mediator 12-(S)-hydroxyeicosatetraenoic acid (12-(S)-HETE), improves post-MI survival, through the biosynthesis of endogenous mediators epoxyeicosatrienoic acids (EETs; cypoxins) to resolve post-MI inflammation. However, the mechanism that amplifies cypoxins-directed cardiac repair in acute heart failure (AHF) and chronic HF (CHF) remains of interest in MI-directed renal inflammation. Therefore, we determined the role of EETs in macrophage-specific receptor activation in facilitating cardiac repair in 12/15LOX deficient mice experiencing HF. Methods and Results: Risk-free young adult (8 -12 week-old) male C57BL/6J wild-type mice (WT; n = 43) and 12/15LOX(-/-) mice (n = 31) were subjected to permanent coronary artery ligation and monitored at day (d)1, d5 (as acute HF), and d28 to d56 (8 weeks; chronic HF) post-surgery maintaining no-MI mice that served as d0 naïve controls. Left ventricle (LV) infarcted area of 12/15LOX(-/-) mice displayed an increase in expression of prostanoid receptor EP4 along with monocyte chemoattractant protein-1 CCL2 in AHF and CHF. The transcriptome analysis of isolated leukocytes (macrophages/neutrophils) from infarcted LV revealed a higher expression of EP4 on reparative macrophages expressing MRC-1 in 12/15LOX(-/-) mice. Deletion of 12/15LOX differentially modulated the miRNA levels, downregulating miR-23a-3p (~20 fold; p < 0.05) and upregulating miR-125a-5p (~160 fold; p < 0.05) in AHF which promoted polarization of the macrophages towards reparative phenotype. Furthermore, 12/15LOX deletion markedly attenuated renal inflammation with reduced levels of NGAL and KIM-1 and apoptotic markers in the kidney during CHF. Conclusion: In risk-free mice during physiological cardiac repair, absence of 12/15LOX promoted reparative macrophages with marked activation of EP4 signaling thereby improving post-MI survival and limiting renal inflammation in acute and advanced HF. The future studies are warranted to advance the role of EETs in macrophage receptor biology.